Formation, stability and dissociation dynamics of N2n+ cations (n = 1 − 2) in 3.5 keV e−-N2 collisions studied using the energy resolved electron–ion coincidence technique. (15th March 2018) - Kumar, S; Prajapati, S; Singh, B; Singh, B K; Shanker, R
Abstract: Coincidences between energy selected electrons and ions produced in the decay of a core hole ionized (excited) state in a free nitrogen molecule have been measured at three specified energies of emitted electrons to reveal the individual pathways produced in 3.5 keV electron-induced fragmentation processes. From these measurements, it has been possible to show, for the first time, that in addition to the normal Auger decay, the resonant Auger excitation channels also share their appreciable contributions in producing singly charged parent ions in an electron-induced collision system. The correlations between ion fragmentation products and electronic structures with a hole configuration in singly-, doubly- and possibly in triply charged molecular electronic states populated in the electronic decay of the initial core hole have been studied and discussed. KER values obtained from our experiments are found to be consistent with the previous results of photo absorption experiments for fragmentation channel N 2 2 +  → N +  + N + ; however, N 2+ fragment ions are found to arise mainly from the fragmentation channel N 2 2 +  → N 2+  + N and to possess relatively low kinetic energies in the considered region of binding energies.